Survey of slug-parasitic nematodes in East and West Flanders, Belgium and description of Angiostoma gandavensis n. sp. (Nematoda: Angiostomidae) from arionid slugs. (2020) - Singh, P.R.; Couvreur, M.; Decraemer, W.; Bert, W.
Abstract: A survey for slug-associated nematodes in five locations of East and West Flanders in Belgium revealed the presence of one new and six known slug-parasitic nematodes, Agfa flexilis (Dujardin, 1845), Alloionema appendiculatum (Schneider, 1859), Angiostoma dentiferum (Mengert, 1953), Angiostoma limacis (Dujardin, 1845), Angiostoma norvegicum (Ross et al ., 2017) and Phasmarhabditis hermaphrodita (Schneider, 1859). Angiostoma norvegicum and P . hermaphrodita are recorded for the first time in Belgium. The six known species are documented by light microscopy (LM) microphotographs and informative DNA sequences. Angiostoma gandavensis n. sp. (Angiostomatidae), discovered from arionid slugs, is described based on light microscopy, scanning electron microscopy (SEM) and molecular data. Based on analyses of D2D3 expansion segment of 28S and 18S rDNA sequences, this new species is found to be related to A . limacis, A . norvegicum, A . margaretae (Ross et al ., 2011) and A . milacis (Ivanova and Wilson, 2009). The new species can be distinguished from these others based on morphological characters such as the distinctive mucronate structures at the tail tip of both sexes, presence of lateral ala, reflexed female ovaries and the number and arrangement pattern of male genital papillae.